Design and Evaluation of a Blockchain-Based Smart Contract Model for Wellness Tourism Services - Sunu Jatmika; Samsul Arifin (International Journal of Electrical and Intelligent Engineering, 2025)
Spa services in wellness tourism often face limitations in transparency, service integration, and customer trust in operational flows. This study develops a blockchain-based smart contract model that integrates five key indicators: reservations, cancellations, customer satisfaction, inventory, scheduling, and finance. A literature review of 113 articles yielded 25 key references, with significant trends such as the occurrence of the keyword “customer reservation” 10,100 times (2020–2024). Linear regression, correlation analysis, and ANOVA methods were used to test the research results. Linear regression predicts the relationship between variables, while correlation measures the strength of the relationship. The calculation results show a Pearson correlation coefficient of 0.93 (α = 0.05), indicating a very strong linear relationship. ANOVA shows significant differences between groups. These findings confirm that blockchain-based smart contracts are effective in digitally automating spa service workflows, strengthening transparency, and improving customer satisfaction